Japanese Women and Sport Beyond Baseball and Sumo - Kietlinski, Robin (Globalizing Sport Studies, 2011)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. In 'Japanese Women and Sport', Robin Kietlinski sets out to problematize the hegemonic image of the delicate Japanese woman, highlighting an overlooked area in the history of modern Japan. Previous studies of gender in the Japanese context do not explore the history of female participation in sport, and recent academic studies of women and sport tend to focus on Western countries. Kietlinski locates the discussion of Japanese women in sport within a larger East Asian context and considers the socio-economic position and history of modern Japan. Reaching from the early 20th century to the present day, Kietlinski traces the progression of Japanese women's participation in sport from the first female school for physical education and the foundations of competitive sport through to their growing presence in the Olympics and international sport.